THE PERCEPTION OF SEMESTER 4 ACCOUNTING STUDENTS ON LEARNING ENGLISH THROUGH WHATSAPP APPLICATION - Kristina Estisari (Universitas Teknokrat Indonesia, 2021)
The pandemic due to the Covid 19 virus has brought all kinds of learning processes into a new era of online and mobile learning. One application that is widely used in online learning is WhatsApp. WhatsApp is not only easy to use because it can be operated via a mobile phone or operated via a personal computer or laptop, but also has features that support the English learning process. This research aimed to determine the perception of 4th semester students majoring in Accounting towards learning English through WhatsApp application at STIE Gentiaras, Bandar Lampung. This research was a quantitative descriptive research. The data was obtained using a questionnaire given to respondents online via Google Form. The population and sample of this research were 34 4th semester students majoring in Accounting. The data were analyzed using a Likert Scale and processed using SPSS 22. The results of the research were divided into 3 dimensions. However, 35.3% of students are doubt whether online learning is more comfortable than offline learning. From the results of the analysis, it can be concluded that the perception of 4th semester students majoring in Accounting at STIE Gentiaras Bandar Lampung towards learning English through the Whatsapp application is positive.